Data protection: the protection of personal information in Zambia - Syanziba, Lynn Munyebo Bwampu (Department of Commercial Law, 2026)
The recognition of the increase in potential threats to personal privacy in the world today accounts for the world's grappling with ways of ensuring that personal privacy is upheld through various means. The perceived threat is being fuelled by 'pervasive deployment of computer systems together with the exponential increase in data collection, data processing, storage and exchange.'